2019
DOI: 10.1097/01.aoa.0000557667.40775.ad
|View full text |Cite
|
Sign up to set email alerts
|

Trainability of Cricoid Pressure Force Application: A Simulation-based Study

Abstract: (Anesth Analg. 2019;128:109–116) Cricoid pressure (CP) force has been suggested as a protective means of preventing aspiration of gastric contents during anesthesia. It is widely used for rapid sequence intubation (RSI). Current national guidelines recommend the use of 10 N when the patient is awake, increasing to 30 N once the patient loses consciousness (LOC). However, studies have shown that few clinicians are proficient at achieving such targets, and individual learning curves during simulation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Other researchers have reported similar observations when studying the knowledge and practice of CP application. [17][18][19][20][21] Noll et al found that only 1.3% of anesthetic physicians and assistants who frequently applied CP could achieve the pressure of 30 Newtons and maintain it during endotracheal intubation. 17 In another study, Koziol et al reported that a large number of their study participants could not identify the cricoid cartilage on a model, only 5% were aware of the correct amount of pressure to be applied, and only 13% of them practically applied the correct amount of pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers have reported similar observations when studying the knowledge and practice of CP application. [17][18][19][20][21] Noll et al found that only 1.3% of anesthetic physicians and assistants who frequently applied CP could achieve the pressure of 30 Newtons and maintain it during endotracheal intubation. 17 In another study, Koziol et al reported that a large number of their study participants could not identify the cricoid cartilage on a model, only 5% were aware of the correct amount of pressure to be applied, and only 13% of them practically applied the correct amount of pressure.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21] Noll et al found that only 1.3% of anesthetic physicians and assistants who frequently applied CP could achieve the pressure of 30 Newtons and maintain it during endotracheal intubation. 17 In another study, Koziol et al reported that a large number of their study participants could not identify the cricoid cartilage on a model, only 5% were aware of the correct amount of pressure to be applied, and only 13% of them practically applied the correct amount of pressure. 18 Clark and Trethewy assessed effective CP application in emergency department physicians and nurses by placing a laryngotracheal model on a scale.…”
Section: Discussionmentioning
confidence: 99%